Effect of graphite flake and multi‐walled carbon nanotube on thermal, mechanical, electrical, and electromagnetic interference shielding properties of polycarbonate nanocomposite. Issue 8 (12th May 2021) - Pradhan, Subhransu S.; Unnikrishnan, Lakshmi; Mohanty, Smita; Nayak, Sanjay K.
Abstract: The current study reports the preparation of polycarbonate (PC) nanocomposite using graphite flake (GF) and multi‐walled carbon nanotube (MWCNT) at varying weight percentages (10%, 20%, and 30%) by the melt mixing technique. The impact of filler on the properties of thermal conductivity (TC), electromagnetic interference shielding (EMI), electrical, and mechanical of the nanocomposite were studied. The improvement in the thermal conductivity value of ˃150% was achieved at a loading of 30% of graphite flake and 20% multiwalled carbon nanotubes. The morphology of the composite studied by field emission scanning electron microscope (FESEM), confirmed the dispersion of filler in the PC matrix. The electrical conductivity of both the optimized compositions achieved was in the order of 10 −2 S/cm. Further, the EMI shielding of ∼35 and ∼32 dB was observed for graphite flake and MWCNT based composites, indicating the suitability of the developed system for various commercial applications. Abstract :